Citrulline for urea cycle disorders in Japan. Issue 4 (22nd December 2016) - Tanaka, Kenichi; Nakamura, Kimitoshi; Matsumoto, Shirou; Kido, Jun; Mitsubuchi, Hiroshi; Ohura, Toshihiro; Endo, Fumio
Abstract: Background: The amino acidl ‐citrulline is used as a therapeutic agent for urea cycle disorders (UCD) including ornithine transcarbamylase deficiency (OTCD), carbamoyl phosphate synthetase I deficiency (CPSD), and N ‐acetylglutamate synthase deficiency. There are few reports, however, on the use ofl ‐citrulline in Japan and little consensus regarding the effects ofl ‐citrulline. Methods: We conducted a questionnaire survey of patients undergoingl ‐citrulline treatment for a UCD to evaluate the current status of this therapy. The survey included patient background, details ofl ‐citrulline treatment, clinical examination data, treatment, frequency of vomiting, and liver transplantation. Results: We retrospectively investigated 43 questionnaire respondents (OTCD, n = 33; CPSD, n = 10). The weight of male OTCD patients improved by +0.79 SD, and the ammonia level decreased by a mean of 44.3 μmol/L in all patients. The protein intake of all patients and of male OTCD patients increased by 0.14 g/kg/day and 0.17 g/kg/day, respectively. Conclusions: l ‐Citrulline effectively reduced ammonia level, increased protein intake, and improved weight gain in UCD patients.l ‐Citrulline should be considered a standard therapy in OTCD and CPSD patients.